2017
DOI: 10.1111/aen.12290
|View full text |Cite
|
Sign up to set email alerts
|

First detection of etoxazole resistance in Australian two‐spotted mite Tetranychus urticae Koch (Acarina: Tetranychidae) via bioassay and DNA methods

Abstract: Etoxazole is used in Australia to control mites on a range of crops including pome fruit and cotton. Although resistance has been widely reported elsewhere, it has not previously been detected in Australia. Here, we report the first detection of etoxazole resistance (>12 500 fold) in Australian two‐spotted mite Tetranychus urticae from pome fruit via both bioassay and DNA methods. It is envisaged that the DNA‐based method developed here can be used to monitor etoxazole resistance in T. urticae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…The CHS1 mutation has been previoulsy reported in only one strain from Turkey (Ilias et al 2014), but without matching toxicity data. Although significant fitness cost has been reported in the presence of the I1017F mutation (Bajda et al 2018), the mutation has been reported in T. urticae strains from different continents (Demaeght et al 2014;Ilias et al 2014;Adesanya et al 2018;Herron et al 2018). With regard to resistance management, our data suggest that more modern CHS1 inhibitors, like etoxazole that is in use throughout Europe, are not a good option to control T. urticae population in Turkey.…”
Section: Discussionmentioning
confidence: 70%
“…The CHS1 mutation has been previoulsy reported in only one strain from Turkey (Ilias et al 2014), but without matching toxicity data. Although significant fitness cost has been reported in the presence of the I1017F mutation (Bajda et al 2018), the mutation has been reported in T. urticae strains from different continents (Demaeght et al 2014;Ilias et al 2014;Adesanya et al 2018;Herron et al 2018). With regard to resistance management, our data suggest that more modern CHS1 inhibitors, like etoxazole that is in use throughout Europe, are not a good option to control T. urticae population in Turkey.…”
Section: Discussionmentioning
confidence: 70%
“…2004; Herron et al . 2018). A second reference strain of T. urticae known as Nashee p was field collected in 2015 from a commercial fruit crop at Banbartha, Victoria, and carries the I1017F mutation in chitin synthase (CHS1) that causes etoxazole resistance (Herron et al .…”
Section: Methodsmentioning
confidence: 99%
“…A second reference strain of T. urticae known as Nashee p was field collected in 2015 from a commercial fruit crop at Banbartha, Victoria, and carries the I1017F mutation in chitin synthase (CHS1) that causes etoxazole resistance (Herron et al . 2018). A reference strain of T. lambi known as Carb that is insecticide susceptible was collected from cotton in Boggabilla, NSW, in 2017.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It acts as a mite growth inhibitor and inhibits chitin synthesis in embryonic and immature stages (Demaeght et al, 2014;Van Leeuwen et al, 2012). There are many reports of etoxazole resistance in spider mites (Adesanya, et al, 2018;Demaeght et al, 2014;Herron et al, 2018;Lee et al, 2004;Wu et al, 2019). In T. urticae, an amino acid substitution of isoleucine to phenylalanine at position 1017 (I1017F) in the chitin synthase 1 gene (CHS1) has been confirmed to confer strong etoxazole resistance (Demaeght et al, 2014;Douris et al, 2016;Herron et al, 2018;Riga et al, 2017;Van Leeuwen et al, 2012;Wu et al, 2019).…”
Section: Several Chemical Classes Of Acaricides With Different Modes mentioning
confidence: 99%